Nickel Mining Business Problems and the Solution in Indonesia - Ji Liang; Jiang Liangliang (Budapest International Research and Critics University, 2023)
This study reviews the problems regarding the principle of industrialization benefits in the management of nickel by mining companies in Indonesia. Nickel management carried out by mining companies must provide benefits for companies, communities, and for the country. The problems and impacts of the nickel mining industry are serious issues that must be considered by the government in relation to environmental damage and employment. For this reason, nickel management by companies based on environmental social governance and downstream programs has become a new concept in nickel management so that nickel resources in Indonesia can attract companies to do business in Indonesia and increase the level of welfare of the Indonesian people. The purpose of this research is to find out and analyze related to the implementation of environmental social governance and downstream in the management of nickel by mining companies in Indonesia. The research method used is qualitative with a descriptive approach. The results of this study indicate that the principle of industrialization benefits in managing nickel by mining companies can be realized if mining companies are able to apply the concept of environmental social governance in managing nickel. The concept of environment social governance in managing nickel does not only pay attention to the environment, but mining companies are required to pay attention to social and corporate governance in managing nickel.